1985
DOI: 10.1172/jci111721
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal polypeptide-induced chloride secretion by a colonic epithelial cell line. Direct participation of a basolaterally localized Na+,K+,Cl- cotransport system.

Abstract: We have used a well-differentiated human colonic cell line, the T4 cell line, as a model system to study the pathways of cellular ion transport involved in vasoactive intestinal polypeptide (VIP)-induced chloride secretion. A modified Ussing chamber was used to study transepithelial Na' and Cl-fluxes across confluent monolayer cultures of the T84 cells grown on permeable supports. In a manner analogous to isolated intestine, the Addition of VIP caused an increase of net Cl-secretion which accounted for the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(107 citation statements)
references
References 53 publications
7
100
0
Order By: Relevance
“…This correlates with the observation in filter-grown monolayers of T 84 cells, a mammalian intestinal cell line, where it has been found that VIP, which activates adenylate cyclase, increased not only the secretory serosato-mucosa flux but also the Cl − flux from mucosa to serosa, suggesting an increase of the diffusional, paracellular pathway in addition to the transcellular Cl − secretion [9]. In HT-29cl.19A cells (another model intestinal cell line), the conductance of the transcellular pathway can reach its maximum while the transepithelial conductance continues to increase.…”
Section: The Modulation Of the CL − Conductance Of The Tight Junctionsupporting
confidence: 89%
See 1 more Smart Citation
“…This correlates with the observation in filter-grown monolayers of T 84 cells, a mammalian intestinal cell line, where it has been found that VIP, which activates adenylate cyclase, increased not only the secretory serosato-mucosa flux but also the Cl − flux from mucosa to serosa, suggesting an increase of the diffusional, paracellular pathway in addition to the transcellular Cl − secretion [9]. In HT-29cl.19A cells (another model intestinal cell line), the conductance of the transcellular pathway can reach its maximum while the transepithelial conductance continues to increase.…”
Section: The Modulation Of the CL − Conductance Of The Tight Junctionsupporting
confidence: 89%
“…This is corroborated by the observed ion selectivity of the tight junctions as determined from the mucosal dilution potentials. Figure 9 shows the relation between the dilution potential (mean 7.6 ± 0.3 mV, n ‫ס‬ 55) and the initial resistance (mean 22.5 ± 0.8 ohm ⅐ cm 2 , 1.5 ± 0.4 (7) 1.5 ± 0.5 (9) Control fluxes were calculated from samples taken at t ‫ס‬ 30 and t ‫ס‬ 40 min after start of experiment. dBcAMP or dBcAMP + bumetanide were added thereafter.…”
Section: Effect Of Camp On Ion Fluxesmentioning
confidence: 99%
“…T84 cells were raised on collagen-coated permeable filters and mounted in custom-made Ussing chambers for measurement of transepithelial chloride secretion as described (15,25). The buffer in the basolateral reservoir was a KrebsRinger solution (pH 7.4) (25 mM sodium bicarbonate), containing 10 mM glucose.…”
Section: Methodsmentioning
confidence: 99%
“…Monolayers of T 84 cells were stimulated with VIP (100 nM) for various times (0.5-30 min) before lysis. At this concentration VIP is known to maximally induce epithelial secretory responses (25). Cell lysates were then immunoprecipitated with anti-EGFr antibodies, and immunoprecipitates were Western-blotted with antiphosphotyrosine.…”
Section: Vip Stimulates Tyrosine Phosphorylation Of the Egfr In T 84mentioning
confidence: 99%